(untitled) (UNWE Yearbook, 2023)
The potential of Green (clean) hydrogen is huge. In Europe, total hydrogen demand is expected to grow to more than 45 million tons by 2050. Many sectors – from transportation to heating to heavy industry – are likely to turn to it as they seek to de-carbonize over the next few decades, with investments in the technology already soaring.Clean hydrogen will become a cornerstone of the energy transition and de-carbonization efforts in Europe and around the globe. Green hydrogen (H2) can be used as a renewable fuel or feedstock in all major CO2-emitting sectors, including those where direct electrification is not possible.The paper looks at the potential of green hydrogen becoming the solution, being the missing piece to the Green Deal ambitions of Europe. Europe possesses the technology and certainly can afford to create the right infrastructure to become a leader in applying, producing and the distribution of green hydrogen.